Microcontroller based multi-function control system for essential oil refining - Syamsul, Syamsul; Mardiyanto, Arief; Denti, Amir; Zaini, Halim; Suherman, Suherman; Hanafi, Hanafi (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The research is to design a multi-function control system using a nodemcu esp32 microcontroller to control the temperature and pressure of the essential oil refining steam boiler. Control aims to obtain the efficiency of the use of LPG gas. To increase efficiency, the controller applies fuzzy logic to each distillation function. The control system is based on the distillation time to get the most optimal essential oil yield. The results and duration of the distillation are based on fuzzy logic. Setting temperature and pressure parameters is based on the characteristics of the type of material to be refined. In nutmeg distillation, the temperature is in the range of 110-120 °C and a minimum pressure of 1.5-2.0 bar. In patchouli distillation the temperature is in the range of 100-110 °C and a minimum pressure of 1.0-1.5 bar. For citronella distillation, the temperature is in the range of 100-110 °C and a minimum pressure of 1.0-1.5 bar. The distillation time for each essential oil raw material is different, and the most optimal time is obtained from. The simulation is based on fuzzy logic. The results of the application of the control system in essential oil refining obtained efficiency in the use of gas. The efficiency of nutmeg essential oil distillation is 17.5% with a distillation time of 12 hours. Patchouli essential oil refining efficiency was 15% with 8 hours distillation. And the efficiency of distillation of citronella essential oil is 10% with distillation for 5 hours. The yield produced in the test of 20 kg of materials, namely nutmeg, patchouli and citronella, obtained a yield of 1.0 kg of nutmeg oil, 350 g of patchouli oil and 220 g of citronella oil.